Studies into the Legacy of Daukantas in Eduard Wolter’s Works: The Theme of Apuolė - Gieda, Aurelijus (Senoji Lietuvos literatūra, 2019)
The aim of the article is to discuss some issues of Eduard Wolter’s activity related to the studies into Daukantas’s legacy placing the focus on the historical-archaeological problem of the localisation of Apuolė. First of all, the author takes a look at the relation of Wolter, a Privatdozent at St. Petersburg University, with Daukantas’s creative legacy. Since Wolter’s activities in this field of study were quite broad and comprehensive, only part of them are addressed. Presented in this article is the history of the search for Apuolė from 1883 to 1887. Through Wolter’s texts and his person, this search is directly related to Dauktantas’s early insights as to where the centre of the Curonian tribe mentioned in a ninthcentury source should be looked for. The article presents a consistent analysis of Wolter’s report of the 1887 expedition to Lithuania and Žemaitija (Samogitia), in which, for the first time in his work, he gives considerable attention to Daukantas. Wolter held the view that apart from the original language and unique ethnographic qualities of the character, Lithuania and Žemaitija had their specific attention-capturing archaeological heritage. Wolter maintained close contacts with all major searchers of the location Apulia even before it had been associated with the Apuolė hill fort in Telšiai County. The article introduces the works by Wolter’s professor Ernst Kunik and by Julius Döring and August Bielenstein, his colleagues from Jelgava on the identification of Apuolė that had appeared before Wolter’s studies. It is interesting that Kunik, a member of the Russian Academy of Sciences, had published his work in a prestigious journal of the Bavarian Academy of Sciences in 1844; he received the proposal to publish his work from and communicated with Georg Waitz and Wilhelm Wattenbach, recognised professionals in the publishing of European historical sources. In December 1887, Wolter published an article specifically devoted to the problem of the localization of Apulia in the Rigasche Zeitung, a daily newspaper of Riga. In it, he recalled the publications by Bielenstein and Döring that had appeared in the same newspaper a year ago (in 1886) in which they developed the version of ‘Apuolė near Skuodas’. Wolter wrote that at the time, only one thing was clear: in his work on the antiquity of Lithuania, ‘the national writer Simonas Daukantas, born in Lenkimai’ clearly indicated the location Apuolė, without any need for further comment. Very likely, these ‘extraordinary insights of Daukantas’ were forgotten because they were written in a Lithuanian language hardly accessible to anyone. Wolter’s publication attracted the attention of his other collaborators who wrote texts with references to Daukantas. For this reason, the author of the article points out that in Lithuanian historiography, the discovery of Apuolė was for some time mistakenly connected with the reading of Daukantas’s works and the subsequent expedition to Skuodas. The author argues that the events might have happened in reverse order: a search had been launched for a site in which Apulia could have been localised; the idea to explore Skuodas was based on the verbal information available at the time and on maps; the hill fort of Apuolė and the site of the old settlement were identified in a specific area of Apuolė by linking the site with the ninth-century Apulia; only then adequate attention was given to the episodes in Daukantas’s historical works that proposed such assumptions (Apulia = Apuolė). In 1919, a manuscript of a historical work written in Lithuanian by an unidentified author in 1822 was found. Wolter examined the manuscript of ‘Darbai’ (Works) and identified its author. For internal criticism, he ingeniously used the comparison of Daukantas’s Apuolė storylines. Thus it turned out in 1920 that Daukantas provided the answer regarding the location of Apuolė 65 years before the official response given by formal late-nineteenth-century scholarship (in 1887). 19th century scientists searched extensively for Seeburg and Apulia, the Curonian locations attacked by the Swedish king with a large army in 853 AD and mentioned in Vita Sancti Anscharii (The Life of St Anscharius) by Rimbert, Archbishop of Bremen-Hamburg, in the ninth century. The greatest merit in this search went to the Courland Society for Literature and Art (Kurländischen Gesellschaft für Literatur und Kunst), which operated in Jelgava (Mitau). On 20 June 1887, during a comprehensive expedition that was also attended by Wolter, Apulia castle was localised in Apuolė hill fort. In his numerous later works, Wolter emphasised with awe and admiration that scholars long sought what Daukantas, a Lithuanian-Samogitian writer, had known much earlier.